Compiled catalogue of the MK spectral classifications, including astrometric and photometric data and its application - Rybka, S.P. (Кинематика и физика небесных тел, 2005)
The catalogue constructed as a tool for stellar kinematic analysis is described. It contains up-todate information on spectral classifications in the MK system, positions and proper motions in the ICRS system, as well as BV magnitudes for 169 843 single stars. Astrometry and photometry were mainly selected from the Tycho-2. MK spectral types and luminosity classes were combined after revision of 11 original spectral catalogues, available from CDS. The first results of stellar kinematic analysis based on compiled catalogue are presented.